CLINICAL COURSE, COMPLICATIONS OF THE HEMORRHAGIC FEVER IN CHILDREN WITH RENAL SYNDROME - Z. M. Enikeeva; E. N. Akhmadeeva; R. F. Agzamova (Медицинский вестник Юга России, 2013)
Purpose: evaluation of the peculiarities of clinical course and complications of hemorrhagic fever with renal syndrome in children with various degrees of severity of acute renal injury.Materials and Methods: 220 children with hemorrhagic fever with renal syndrome were examined. The complex estimation of renal functions with using clinical and laboratory methods was made.Results: The peculiarities of the clinical manifestation of the disease in various periods of a course of hemorrhagic fever with renal syndrome, development of acute renal injury: severe in 24.5%, moderate in 40%, mild in 35.5%, the possibility of lifethreatening complications in children in oligo-anuricheskoy phase of severe acute kidney injury were established.Summary: Hemorrhagic fever with renal syndrome (HFRS) in children has a cyclic clinical course, complicated by the development of acute kidney injury by the end of the feverish period. The development of infectious-toxic shock, disseminated intravascular coagulation (DIC), cerebral edema with dislocation syndrome can lead to fatal outcome.